Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1073/pnas.1703295114
|View full text |Cite
|
Sign up to set email alerts
|

Large-moment antiferromagnetic order in overdoped high- T c superconductor 154 SmFeAsO 1− x D x

Abstract: In iron-based superconductors, high critical temperature (T c ) superconductivity over 50 K has only been accomplished in electron-doped hREFeAsO (hRE is heavy rare earth (RE) element). Although hREFeAsO has the highest bulk T c (58 K), progress in understanding its physical properties has been relatively slow due to difficulties in achieving high-concentration electron doping and carrying out neutron experiments. Here, we present a systematic neutron powder diffraction study of 154 SmFeAsO 1−x D x , and the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
0
20
1
Order By: Relevance
“…It was our surprise to see a structural transition from the tetragonal to a unique orthorhombic structure in AFM2 phase( Fig. 1b) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was our surprise to see a structural transition from the tetragonal to a unique orthorhombic structure in AFM2 phase( Fig. 1b) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Very similar to the partial substitution of fluorine for oxygen in Ln FeAsO, hydrogen also leads to electron doping (O 2− → H − + e − ) 7 , resulting in a T c of up to ~ 55 K. The distinct difference between H- and F-doping is the substitution limit: x ≤ 0.8 for Ln FeAsO 1− x H x 8 in contrast to x ≤ 0.2 for Ln FeAsO 1− x F x 9 . Furthermore, a high T c of ~ 50 K is maintained in the range 0.13 < x < 0.43 for Ln FeAsO 1−x H x 7 .…”
mentioning
confidence: 99%
“…The growth of Ln FeAs(O,H) opens new opportunities to explore how heavily electron doping influences the superconducting properties. However, most of the studies have been carried out on polycrystals 7 , 8 or tiny single crystals 10 , on which measurements of the transport critical current density are rather complicated. The successful growth of Ln FeAs(O,H) epitaxial thin films gives a great opportunity to explore the intrinsic physical properties by electrical transport measurements especially for critical current characteristics, since thin films are the ideal platform for such investigations.…”
mentioning
confidence: 99%
“…Recently, a doping technique for producing a higher electron concentration for 1111 systems has been developed in which H − is used instead of F − [17][18][19][20]. Remarkably, owing to the heavy electron doping, a second antiferromagnetic phase appears in La-and Sm-1111 systems just after disappearance of the superconducting phase [21,22]. Several subsequent studies have all suggested that the heavy electron doping enhances electron correlations and the localized character in the second antiferromagnetic phase [8,19,20,[23][24][25].…”
mentioning
confidence: 99%
“…Several subsequent studies have all suggested that the heavy electron doping enhances electron correlations and the localized character in the second antiferromagnetic phase [8,19,20,[23][24][25]. These studies suggested that spin and/or orbital fluctuations from the strongly correlated phase significantly contribute to the high T c in 1111 compounds [15,16,21,22]. Therefore, it is indispensable to understand magnetic excitations in the heavily electron-doped antiferromagnetic phase.…”
mentioning
confidence: 99%